Activation of the interleukin‐6/Janus kinase/STAT3 pathway in pleomorphic adenoma of the parotid gland. Issue 8 (8th June 2015) - Andreasen, Simon; Therkildsen, Marianne Hamilton; Grauslund, Morten; Friis‐Hansen, Lennart; Wessel, Irene; Homøe, Preben
<x xml:space="preserve">Abstract</x> The interleukin‐6 (IL‐6)/Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) pathway is of crucial importance in promoting tumorigenesis in several malignant tumors but may also be active in benign tumors, e.g., of pleomorphic adenoma (PA). In this study we characterize the expression of the pathway components with immunohistochemistry and selected mRNAs and microRNAs (miRNAs) regulated by this pathway in isolated duct‐ and myoepithelial cells in PA. 46 PAs were immunostained and 10 of these were used for in situ hybridization (ISH). Six frozen specimens were analyzed using reverse transcription‐polymerase chain reaction (RT‐PCR). Using immunohistochemistry, IL‐6, JAK1, JAK2 and STAT3 were detected significantly more frequently in PA cells than in cells from normal salivary gland tissue. Using RT‐PCR cyclin D1, fibroblast growth factor 2, and p21 were found to be overexpressed while matrix metallopeptidase 9 was detected at low levels in PA compared to normal salivary gland. ISH showed significant overexpression of miR‐181b in PA, while miR‐21 was undetectable in PA and normal tissue. Overexpression of the pathway components and its mRNA and miRNA products provide important clues regarding the growth of PAs. Our findings brings us one step closer to targeted treatment of this tumor entity, although in vitro studies are warranted to confirm this.